COMBINING ABILITY FOR QUANTITATIVE ATTRIBUTES IN LABLAB BEAN (Lablab purpureus L.) (Bangladesh Journal of Plant Breeding and Genetics, 2008)
General (GCA) and specific (SCA) combining ability for ten quantitative characters of seven parental genotypes and 21 F1s derived from a 7x7 diallel cross without reciprocal was assessed. Combining ability analysis following Griffing,s approaches suggested the association of both additive and non-additive gene action in the genetic system with the preponderance of additive gene effect in the expression of all the traits except number of inflorescences per plant. The non-additive genetic component was exclusive or predominant for inflorescence per plant. Ranking of the parents for ten characters on GCA performance indicated that the parental genotype DS-7 was the best general combiner for pollen sterility percent, 10-green pod weight, 20-seed weight and the genotype DS-27 for the trait pod yield per plant. The estimates of SCA effect revealed that in most of the cases, combinations of high x low or even low x low exhibited high SCA effect for many characters rather than high x high cross combinations indicating the importance of gene interaction. Based on SCA performances the crosses S12 x S11 and DS-164 x DS-27 were the best specific combiners for days to 1st flowering. The crosses DS-164 x S12, DS-52 x S11, DS-164 x DS-9(t) were the best specific combinations for pollen sterility percent, pod length, and pod yield per plant respectively.DOI: http://dx.doi.org/10.3329/bjpbg.v21i1.17046